Untargeted metabolomics towards understanding molecular mechanisms of pulmonary arterial hypertension. (14th October 2021) - Wawrzyniak, R; Dabrowska-Kugacka, A; Macioszek, S; Gockowska, I; Biesemans, M; Furga, A; Zieba, B; Lewicka, E; Markuszewski, M
Abstract: Background: Pulmonary hypertension constitutes a rare disease characterized by a severe development and a high risk of premature death. One of its main clinical types is pulmonary arterial hypertension (PAH), in which the highest percentage of patients are affected by idiopathic PAH. The pathogenesis of this disease has not completely been discovered and elucidated so far, and non-specific clinical symptoms make the diagnosis of PAH a serious problem. Currently, PAH is confirmed with invasive examination based on right heart catheterization. Purpose: The main aim of the study was to evaluate and compare both plasma and urine fingerprints of PAH patients and control group with the use of an untargeted metabolomics approach. The study also focused on correlation analysis between the observed metabolic changes and the clinical parameters to select specific indicators of PAH disease. Methods: An untargeted metabolomics approach was applied to the plasma and urine samples with the use of gas chromatography coupled to triple quadrupole mass spectrometry (GC-QqQ/MS) and advanced statistical tests were applied to evaluate the potential metabolic indicators of PAH. The PAH patients (n=40) and healthy controls (n=39) were matched for age, sex, BMI and included in the study. The obtained raw datasets were properly processed (data deconvolution, signal correction using QCSVR method and PQN normalization) and subsequently subjected to uni- and multivariate statistical tests (Student's t-test, Welch's test, U Mann-Whitney test, PCA and OPLS-DA). The identification of the statistically significant metabolites was performed using universal libraries, such as: Fiehn's and NIST11. Results: The statistically significant metabolites (n=10 and 11 for urine and plasma samples, respectively)originate from various biochemical pathways associated with the carbohydrate, amino acid, lipid, fatty acid and pyrimidine metabolism. The metabolic changes observed in the urine samples of PAH patients (compared to the control group) included different concentrations in: threonic acid, hippuric acid, acetic acid, sorbitol, butanoic acid and propionic acid. The metabolic alterations in the plasma samples covered changes in the levels of valine, leucine, lactic acid, hydroxybutanoic acid, nonanoic acid, cholesterol and octadecanoic acid. Metabolites representing the highest correlation with mean pulmonary arterial pressure include, for instance: propionic acid (r=0.85), valine (r=0.75) and lactic acid (r=0.63) Conclusions: The observed metabolic changes are related to various biological processes that are disturbed in the course of PAH, namely: proliferation of pulmonary vascular cells or the functions of cardiomyocytes and the right ventricle of the heart. The obtained results confirmed the potential of a metabolomics approach to uncover and explain the underlying molecular mechanisms of PAH. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Science and High Education of Poland